PENGARUH PEMBERIAN MINYAK BUAH MERAH (Pandanus conoideus Lam.) TERHADAP DEGENERASI SEL GINJAL MENCIT (Mus musculus) YANG DIPAPAR PLUMBUM - novarina sullsia; Siska Aprilianti; Maratun Janah; Candra Dwi Atma (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2020)
Plumbum (Pb) pollution in environment can cause dangerous for animal. Plumbum enter the body through oral cavity and was excreted by kidney and can effect to the kidney function. Defect in kidney can make distraction of metabolism. An effort to prevent deffect in kidney that cause by plumbum can be used antioxidant from Red Fruit plant (Padanus conoideus Lam). The aim of this research was to know the effect of Red Fruit plant with the degrees of kidney cell degeneration that was exposed by plumbum. Type of this research was experimental research that use complete random design with 4 treatment, P0 (aquadest 0,5 ml), P1 (Pb 0,01 mg), P2 (was given with Red Fruit Oil 0,3 ml and Pb 0,01 mg), P3 (was given with Red Fruit Oil 0,8 ml and Pb0,01 mg). The data was analyzed by Kruskal Wallis using SPSS and followed with Mann-Whitney test. The result of this research show that there were significant difference between P0 and P1, P0 and P2, P0 and P3, P1 and P3 (P<0,05), but did not showed significant difference (p>0.05) with P2 and P3. Base on this research can be concluded that giving red fruit oil can decrease the degrees of cell degeneration in mouse kidney that was exposed by plumbum.